Kriptal Consignor's Efforts To Increase Competitiveness Through Consignment Sales System - Yesi Indian Ariska; Nirta Vera Yustanti; Siti Hanila (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The consignment sales system is one of the marketing strategies that can be carried out by business actors to expand market reach because with this system business actors do not move alone in making sales. This consignment system is a system where business actors who have goods leave the goods/products to the shop owner (consignee). This research was conducted to provide an overview of the consignment sales system carried out by KriptaL business actors and provide an overview of the impact of consignment sales on the competitiveness of KriptaL products. This research uses observation, interview and documentation methods to explain the data, while the object of research is the KriptaL snack business in Bengkulu City. Based on the research conducted and discussion, it can be concluded that in the KriptaL business the consignor sales agreement is in accordance with the agreement including the agreement regarding the price level, the amount of commission or reward, the number of products entrusted and returns on sales, KriptaL consignor business in increasing competitiveness has a positive impact on the KriptaL business and the store. Where this can be seen from the expansion of the marketing network, the increase in turnover of business actors, in terms of profit or profit and more advanced technology.